Cultural Hero and Personage: Representation in Contemporary Visual Art of Ukraine - Sydorenko, Victor (Journal of History Culture and Art Research, 2020)
The article focuses on the research of the semantic links between the concepts of a cultural hero and a personage, on substantiation of their existence and representation in the context of social and artistic processes of the visual art of Ukraine. I shall argue that artistic conceptualization of non-hierarchical “personages” is an ongoing issue in contemporary art. Ukrainian artists in their projects continue experiments with the boundaries of contemporary personages. Nevertheless, cultural hero, his main roles and functions become situational and processual these days. It was discovered that representativity builds up and corrects the links between the author and the personage of a visual artwork, through approximation or, on the contrary, distancing the author from the personage, when a certain goal of the artist in this artistic communication is revealed. It was concluded that reconstruction—as a representative strategy—aims to recover the authentic foundations of national identity and form the advanced typology of Ukrainian cultural heroes; while deconstruction is aimed at ruining totalitarian senses of Ukrainian culture and demolishing the figure of the cultural hero of Soviet times. In the latter process, both the artist and the character of the visual artwork are anonymized, so that the new foundations of contemporary heroization could be discovered.